Endogenous CXCL9 affects prognosis by regulating tumor‐infiltrating natural killer cells in intrahepatic cholangiocarcinoma. Issue 2 (23rd January 2020) - Fukuda, Yasunari; Asaoka, Tadafumi; Eguchi, Hidetoshi; Yokota, Yuki; Kubo, Masahiko; Kinoshita, Mitsuru; Urakawa, Shinya; Iwagami, Yoshifumi; Tomimaru, Yoshito; Akita, Hirofumi; Noda, Takehiro; Gotoh, Kunihito; et al.
Abstract: CXCL9, an IFN‐γ inducible chemokine, has been reported to play versatile roles in tumor‐host interrelationships. However, little is known about its role in intrahepatic cholangiocarcinoma (iCCA). Here, we aimed to elucidate the prognostic and biological implications of CXCL9 in iCCA. Endogenous CXCL9 expression and the number of tumor‐infiltrating lymphocytes were immunohistochemically assessed in resection specimens. These data were validated in mice treated by silencing CXCL9 with short hairpin RNA. In addition, the induction of endogenous CXCL9 and the effects of CXCL9 on tumor biological behaviors were evaluated in human cholangiocarcinoma cell lines. Immunohistochemical analyses revealed that high CXCL9 expression was closely correlated with prolonged postoperative survival and a large number of tumor‐infiltrating natural killer (NK) cells. In fact, due to the trafficking of total and tumor necrosis factor‐related apoptosis‐inducing ligand‐expressing NK cells into tumors, CXCL9‐sufficient cells were less tumorigenic in the liver than CXCL9‐deficient cells in mice. Although CXCL9 involvement in tumor growth and invasion abilities differed across cell lines, it did not exacerbate these abilities in CXCL9‐expressing cell lines. We showed that CXCL9 was useful as a prognostic marker. Our findings also suggested that CXCL9 upregulation might offer a therapeutic strategy for treating CXCL9‐expressing iCCA by augmenting anti–tumor immune surveillance. Abstract : CXCL9, an IFN‐γ inducible chemokine, plays versatile roles in the tumor‐host interrelationship. In this study, we demonstrated that elevated intratumoral CXCL9 expression was associated with a large number of tumor‐infiltrating NK cells, leading to favorable postoperative survival in patients with intrahepatic cholangiocarcinoma. Upregulation of CXCL9 might be an immunotherapeutic approach for treating intrahepatic cholangiocarcinoma.